2005
DOI: 10.1038/sj.ijo.0802997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture in reducing weight and waist circumference in obese women: a randomized crossover trial

Abstract: OBJECTIVE:To compare the effects of weight control on simple obese women between electroacupuncture and sit-up exercise. DESIGN: Randomized and crossover trial conducted from 1 January 2002 to 31 December 2002. The subjects were randomly divided into groups A and B. Group A received electroacupuncture treatment first while group B received sit-up exercise treatment first. After 6 weeks of treatment and 7 days of washout, group A switched to sit-up exercise treatment and group B received electroacupuncture trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 19 publications
0
59
0
2
Order By: Relevance
“…Allison et al 40 reported three adverse events, namely, redness, pain or discomfort, and bleeding in ears in auricular acupuncture group compared to none in placebo group, although their frequencies were not statistically different. Hsu et al 38 reported no major adverse event; however, mild ecchymosis (n ¼ 2) and abdominal discomfort after electroacupuncture treatment (n ¼ 1) was observed. Richards and Marley 34 reported a case of intercurrent illness and discomfort in a placebo group, whereas Dong 43 reported mild adverse effects, such as dry mouth, headaches, sleepiness, hypertension, palpitations and dizziness, up to 16.7% in the acupuncture group, compared with 42.9% in a group of receiving medication.…”
Section: Acupuncture Versus Wait-list Controlmentioning
confidence: 97%
See 3 more Smart Citations
“…Allison et al 40 reported three adverse events, namely, redness, pain or discomfort, and bleeding in ears in auricular acupuncture group compared to none in placebo group, although their frequencies were not statistically different. Hsu et al 38 reported no major adverse event; however, mild ecchymosis (n ¼ 2) and abdominal discomfort after electroacupuncture treatment (n ¼ 1) was observed. Richards and Marley 34 reported a case of intercurrent illness and discomfort in a placebo group, whereas Dong 43 reported mild adverse effects, such as dry mouth, headaches, sleepiness, hypertension, palpitations and dizziness, up to 16.7% in the acupuncture group, compared with 42.9% in a group of receiving medication.…”
Section: Acupuncture Versus Wait-list Controlmentioning
confidence: 97%
“…A total of 2 RCTs 31,32 provided insufficient information so that 29 RCTs were used for our meta-analysis. Acupuncture for obesity S-H Cho et al described their randomization procedure, [34][35][36][37][38] whereas information of dropout or withdrawal was described in 10 trials (32%). Among 26 trials that did not report the randomization procedure, 20 trials (77%) scored the lowest with respect to methodological quality (Table 1).…”
Section: Study Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For EA the evidence is more positive; the majority of studies suggest that EA induces significantly greater weight loss than sham EA, 18 78 or acupuncture performed at no acupuncture points 85 whereas only one study concluded that EA and exercise resulted in similar reductions in body weight. 77 Effects on obesity-related peptides As already mentioned, obesity is characterised by hyperleptinaemia and leptin resistance. Both manual 72 83 and auricular acupuncture 74 as well as EA 79 83 exert a beneficial effect on leptin resistance and cause a significant decrease in plasma leptin levels in obese patients compared with sham 72 74 or diet alone.…”
Section: Effect Of Different Types Of Acupuncture On Body Weight Alonementioning
confidence: 99%